Color Vision Variation and Foraging Behavior in Wild Neotropical Titi Monkeys (Callicebus brunneus): Possible Mediating Roles for Spatial Memory and Reproductive Status - Bunce, John A.; Isbell, Lynne A.; Grote, Mark N.; Jacobs, Gerald H. (International journal of primatology, 2011)
The selective advantages to primates of trichromatic color vision, allowing discrimination among the colors green, yellow, orange, and red, remain poorly understood. We test the hypothesis that, for primates, an advantage of trichromacy over dichromacy, in which such colors are apt to be confused, lies in the detection of yellow, orange, or red (YOR) food patches at a distance, while controlling for the potentially confounding influences of reproductive status and memory of food patch locations. We employ socially monogamous titi monkeys ( Callicebus brunneus ) which, like most platyrrhine primates, have polymorphic color vision resulting in populations containing both dichromatic and trichromatic individuals. Wild Callicebus brunneus spent most foraging time in YOR food patches, the locations of most of which were likely to have been memorable for the subjects. Overall, both dichromatic and trichromatic females had significantly higher encounter rates than their dichromatic male pair mates for low-yield ephemeral YOR food patches whose locations were less likely to have been remembered. We detected no difference in the encounter rates of dichromatic and trichromatic females for such patches. However, the data suggest that such a difference may be detectable with a larger sample of groups of Callicebus brunneus , a larger sample of foraging observations per group, or both. We propose that a trichromatic advantage for foraging primates may be realized only when individuals’ energy requirements warrant searching for nonmemorable YOR food patches, a context for selection considerably more limited than is often assumed in explanations of the evolution of primate color vision.